The Liberalization of the Law on Resources: The Case Study of the Health Sector Liberalization in the Post-Reformation Era - Zaini, Naya Amin; Dimyati, Khudzaifah; Absori,; Azhari, Aidul Fitriciada; Budiono, Arief (International Journal of Psychosocial Rehabilitation, 2020)
The Reformation Era happened on 1997, which marked the end of the New Order era (1967-197). The Reformation Era is a transitional situation, which may be deemed as chaos, as the social, political, and economic situations trigger chaos and degradation. It impacts the legislative products on natural resources formed post-reformation, where it contains liberal and capitalist legal substances. Thus, in the legal practice, it gives justification and legitimization. There is a shift in the legal sovereignty in the legal characters in strengthening the private and individual sectors. Due to the chaotic situation, there is the condition of cosmos which is the amendment of Article 33 of the Republic of Indonesia’s 1945 Constitution. It inserts paragraphs (4) and (5) as articles of capitalism-liberal legitimization in the constitution. The health sector is the sector which experienced the greatest change into liberalization. The health rights in the constitution are cut through legal liberalization. This research uses a doctrinal paradigm or the juridical-normative method.